2006
DOI: 10.1021/ja062796t
|View full text |Cite
|
Sign up to set email alerts
|

Radical/Ion Pair Formation in the Electrochemical Reduction of Arene Sulfenyl Chlorides

Abstract: Important aspects of the electrochemical reduction of a series of substituted arene sulfenyl chlorides are investigated. A striking change is observed in the reductive cleavage mechanism as a function of the substituent on the aryl ring of the arene sulfenyl chloride. With p-substituted phenyl chlorides a "sticky" dissociative ET mechanism takes place where a concerted ET mechanism leads to the formation of a radical/anion cluster before decomposition. With o-nitropheyl sulfenyl substituted chlorides a stepwis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 46 publications
0
44
0
Order By: Relevance
“…We previously reported the electrochemical reduction of arene sulfenyl chlorides (ArSCl) and showed that their reduction results in the cleavage of the S-Cl bond. 34,63 Our investigation showed that the electrochemical reduction of 4-substituted sulfenyl chlorides follows a sticky dissociative ET mechanism involving the formation of a radical/anion (4-substituted phenyl sulfenyl radical/chloride anion) pair. 34 This manuscript describes the full investigation of an extended series of 4-substituted arene sulfonyl chlorides 1a-g (Chart 1).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…We previously reported the electrochemical reduction of arene sulfenyl chlorides (ArSCl) and showed that their reduction results in the cleavage of the S-Cl bond. 34,63 Our investigation showed that the electrochemical reduction of 4-substituted sulfenyl chlorides follows a sticky dissociative ET mechanism involving the formation of a radical/anion (4-substituted phenyl sulfenyl radical/chloride anion) pair. 34 This manuscript describes the full investigation of an extended series of 4-substituted arene sulfonyl chlorides 1a-g (Chart 1).…”
Section: Introductionmentioning
confidence: 84%
“…The cyano-and nitrosubstituted compounds (1f,g) provide only the corresponding aryl sulfinates and no side products, similar to what has been seen for the nitro substituted arene sulfenyl chlorides. 34 Based on the electrochemical data, and considering, for now, a two electron reductive dissociation of the S-Cl chemical bond, the reduction mechanism for these compounds can be written as per Scheme 1. The sulfinate anion generated through the two electron reduction process transfers an electron to the parent sulfonyl chloride (reaction B).…”
Section: Electrolysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some electrochemical data are also supported by theoretical calculations. This also allows a comparison with arene sulfenyl chlorides that we reported previously (27,28).…”
Section: Introductionmentioning
confidence: 96%